Madelung’s Disease: A Clinical Case and Review of Literature - Niang, Chau Su (Asian Journal of Medical Sciences, 2013)
Madelung’s disease is a rare disease of unknown aetiology. This disease usually affects middle-aged males from Mediterranean area with history of alcohol abuse. We describe an Asian male presented with typical features of Madelung’s disease. Asian Journal of Medical Science, Volume-4 (2013), Pages 33-35 DOI: http://dx.doi.org/10.3126/ajms.v4i4.7968